DETERMINAN FAKTOR YANG MEMENGARUHI KINERJA SISTEM INFORMASI PADA KOPERASI DI KABUPATEN BANYUMAS - Kusuma Wiguna, Muhamad Wisnu; Oktaviana, Amelita; Wiratno, Adi (Jurnal EBI, 2024)
Currently, technological developments are increasingly rapid and sophisticated, one of which is developments in accounting information systems. In this situation, users are required to adapt to current developments in technology because many companies are competing to advance their business. This research aims to determine the variables influencing the performance of accounting information systems in cooperatives in Banyumas Regency. Data was obtained in this research by distributing questionnaires to employees with a total of 106 respondents. The sampling technique uses purposive sampling with certain criteria. The results of this research indicate that user technical abilities, formalization of system development, user training and education programs, and top management support have a positive influence on accounting information system performance, while the work experience variable has no effect.Keywords : performance; accounting information system; cooperative;